Pengaruh Perceived CRM Capability terhadap Purchase Intention pada Penggemar Klub Sepak Bola: Peran Mediasi Fan Engagement dan Moderasi Privacy Concern - Vincenzo Hiroshi; Peter Remy Yosy Pasla; Teofilius Karnalim; Sahala manalu; I Gusti Ngurah Agung Arya Bhakta Narayana (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the influence of Perceived Customer Relationship Management (CRM) Capability on the Purchase Intention of football club fans, with Fan Engagement as a mediating variable and Privacy Concern as a moderating variable. The modern football industry treats fans as strategic assets who contribute financially through tickets, merchandise, and digital content, making a club's ability to manage data-driven fan relationships highly crucial. This research employs an explanatory quantitative approach with a cross-sectional design. Respondents are fans of professional football clubs in Indonesia who actively interact through the clubs' digital platforms, with a minimum target of 150 respondents selected using a purposive sampling technique. Data were collected via an online questionnaire utilizing a 1-5 Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) through SmartPLS 4.0, which includes outer model evaluation, inner model evaluation, mediation testing (bootstrapping indirect effect), and moderation testing (product indicator approach). The results are expected to provide theoretical contributions in the form of empirical evidence regarding the psychological mechanisms linking CRM Capability with fan consumption behavior in an emerging market, while simultaneously offering practical guidance for Indonesian football club management in designing effective, responsible, and sustainable digital CRM strategies.